1994
DOI: 10.1192/s0007125000293045
|View full text |Cite
|
Sign up to set email alerts
|

Randomised-Control Trial of Family Intervention for 78 First-Episode Male Schizophrenic Patients

Abstract: At the time of discharge from their first stay in psychiatric hospital, 78 male schizophrenic patients were randomly assigned to a family intervention (experimental) group or a ‘standard care’ control group and were followed for the next 18 months. The family intervention consisted of both group and individual counselling sessions every 1–3 months that focused on education about the illness and on methods of dealing with the patient. There was a significantly lower rate of hospital readmission in the family in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
167
0
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(175 citation statements)
references
References 10 publications
4
167
0
3
Order By: Relevance
“…This is often an aim in the mutual support group model. 12,13 Nor was this desirable. The goal was to offer a more general model of psychoeducation applicable to multiple diagnoses.…”
Section: Cultural Differencesmentioning
confidence: 99%
“…This is often an aim in the mutual support group model. 12,13 Nor was this desirable. The goal was to offer a more general model of psychoeducation applicable to multiple diagnoses.…”
Section: Cultural Differencesmentioning
confidence: 99%
“…From six studies, information was available on readmission rates for up to 2 years into treatment (Falloon et al 1982 ;Glynn et al 1992 ;Xiong et al 1994 ;Zhang et al 1994 ;Buchkremer et al 1995 ;Schooler et al 1997). Family interventions showed consistent benefits over all other treatments in the number of patients readmitted to hospital, even over this prolonged period.…”
Section: Readmissionmentioning
confidence: 99%
“…Sixteen trials provided data on treatment non-compliance in family interventions compared to all other treatments, including standard care (Goldstein et al 1978 ;Falloon et al 1982 ;Leff et al 1982Leff et al , 1989Hogarty et al 1986Tarrier et al 1988 ;Glynn et al 1992 ;Posner et al 1992 ;Vaughan et al 1992 ;Zhang et al 1994 ;Bloch et al 1995 ;Buchkremer et al 1995 ;Schooler et al 1997).…”
Section: Suicidementioning
confidence: 99%
“…The Zhang et al study (29) demonstrated that family intervention and regular use of medication had independent and additive beneficial effects. The data of Spiegel and Wissler (24) showed that while family consultation in the home for recently discharged schizophrenic patients did not prevent readmission, it did provide a significant decrease in time spent in the hospital for the first 3 months.…”
Section: Clinical Trials With Random Assignment Of Subjectsmentioning
confidence: 99%